Crystallization Behavior of Palm Oil Blends and Palm Oil-Based Fluid Shortenings - Mat Sahri, Miskandar (2006)
This thesis covers the establishment of palm oil-based fluid shortening production by investigating the static and dynamic crystallization behaviors of palm oil blends with and without emulsifier at various temperature treatments. Solid fat content (SFC), crystal size and distribution, fatty acid content (FAC) and triacylglycerol (TAG) composition of the palm oil blends were determined and analyzed using ANOVA at 95% confidence level. Palm oil-based fluid shortening formulation, emulsifier and stirring speed were optimized using response surface methodology (RSM) based on the storage study that included SFC, viscosity, pourability and crystal size and distribution. Crystal development of the blends as a function of time had developed crystallization curves that demonstrated distinct steps corresponding to crystallization stages due to the occurrence of mixed crystallization. Slow crystallization without emulsifier was influenced by the total saturated FAC, with significant (P<0.05) changes in SFC, crystal distribution and viscosity. Lecithin at 0.03% was generally a crystal promoter; however, at 0.06 and 0.09% it acted as a crystal inhibitor. STS was generally a crystal inhibitor at 0.03, 0.06 and 0.09%. Temperature cycling processes at Cycle 3 had caused the blends with slip melting points (SMP) of 26.5 - 33.5°C to crystallize forming uniform crystal aggregates. Crystal size of blends with emulsifier was significantly increased as the temperature cycling was reduced and the emulsifier content was increased. However, blends with 0.03 and 0.06% lecithin and 0.09% STS had low viscosities. Blends of SMP 21.6 - 26.5°C with 0.09% STS and 0.03% lecithin formed crystal aggregates ranging from 10 – 40 μm and produced low SFCs. The model developed by RSM comprising of 20 - 23% palm oil, 77 - 80% palm olein, 0.02-0.06% lecithin and crystallized at stirring speed of 150 – 300 RPM had established palm oil-based fluid shortenings stable at storage of 25 – 30ºC for three weeks. It is concluded that the size of the crystal aggregates and their distribution in the bulk, were important factors contributing to palm oil-based fluid shortening to flow.